2002
DOI: 10.1093/qjmed/95.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Complications and cardiovascular risk factors in South Asians and Europeans with early-onset type 2 diabetes

Abstract: Complications were common at diagnosis, with a quarter of all patients having evidence of at least one diabetic complication. South Asians had a higher prevalence of established macrovascular and microvascular disease, compared to Europeans, and a higher risk of CHD, predominantly because of lower HDL cholesterol and higher blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 12 publications
4
53
0
1
Order By: Relevance
“…58,142,145,149,152,153 Logistic regression analysis of univariate association between glucose tolerance and various anthropometric variables showed a stronger association with waist-hip ratio than BMI. However, the waist-hip ratios were not different among any of the South Asian subgroups.…”
Section: Waist-hip Ratiomentioning
confidence: 95%
See 2 more Smart Citations
“…58,142,145,149,152,153 Logistic regression analysis of univariate association between glucose tolerance and various anthropometric variables showed a stronger association with waist-hip ratio than BMI. However, the waist-hip ratios were not different among any of the South Asian subgroups.…”
Section: Waist-hip Ratiomentioning
confidence: 95%
“…South Asians, in particular females, have lower levels of total cholesterol 58,136,145,155 and highdensity lipoprotein cholesterol-C (HDL-C) 58,153 58 reported high levels of total cholesterol in Sikhs (6.06 mmol/l) and the lowest levels in Gujarati Hindus (5.45 mmol/l; p < 0.001). However, the HDL-C is high among the Sikhs (1.22 mmol/l) and lowest in Muslim men (1.04 mmol/l; p < 0.001).…”
Section: Cholesterolmentioning
confidence: 99%
See 1 more Smart Citation
“…Asian patients have shown evidence of macro-and microvascular disease at the time of diagnosis of diabetes when compared to Europeans. 2 Diabetes is the most common cause of kidney failure, accounting for $44% of new cases. 3 Even when diabetes is controlled, the disease can lead to chronic kidney disease (CKD) and kidney failure.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown increased progression of diabetic retinopathy and maculopathy following extracapsular cataract extraction, 3 whereas following uncomplicated phacoemulsification cataract extraction there is no associated progression of diabetic 4 Studies have also suggested differences in the prevalence of complications secondary to diabetes including retinopathy between various races. 5,6 The UK Prospective Diabetes Study 7 found the prevalence of retinopathy at diagnosis of type II diabetes to be similar between white Caucasian, Asian, and Afro-Caribbean patients. Chatterjee et al 8 present an original piece of work assessing diabetic retinopathy and maculopathy progression along with visual outcome following phacoemulsification cataract extraction in South-Asian and Afro-Caribbean patients who are type II diabetics.…”
mentioning
confidence: 99%